Corrupted: an essay on intellectual character and epistemic vice - Matthews, Taylor Roger Charlie (2024)
This thesis examines the relationship between character and intellectual or epistemic vices. The philosophical study of epistemic vices is called vice epistemology. To date, much of the work in this emerging field has focused on the nature and epistemological significance of particular intellectual vices such as close-mindedness or dogmatism. Far less has been said about how it is that people come to acquire and develop these intellectual vices. My aim is to fill this lacuna by articulating how this phenomenon occurs. Specifically, this thesis develops an account of epistemic corruption. I start in chapter 1 with a critical discussion of character. Despite character forming a foundational pillar of responsibilist virtue epistemology, there is surprisingly little discussion as to what intellectual character might look like. The discussion in this chapter attempts to get clearer on this matter by offering an ontology of character that is both conceptually and empirically robust going forward. In chapter 2, I introduce the phenomenon of epistemic corruption in detail, distinguishing a variety of ways it might occur. Chapter 3 examines how these variants operate in practice by considering the finer mechanics of epistemic corruption. There, I raise difficulties for an existing account and offer solutions to offset these difficulties. In chapter 4, I turn to consider whether collective agents might be susceptible to epistemic corruption. Drawing on Miranda Fricker’s account of institutional character, which she terms ‘institutional ethos’, I distinguish two ways in which this might occur. Ultimately, though, I urge caution about Fricker’s account, and with it, the prospects of applying epistemic corruption to collective agents. Finally, in chapter 5, I raise concerns about a different analogy in virtue theory: the skill-analogy. I argue that this analogy has problematically influenced how vice epistemologists treat skill in their theorising of epistemic vice, resulting in an assumption that the latter will be characterised by an absence or deficit of the former. I refer to this as the deficiency thesis and reject it. In doing so, I note how its rejection provides a novel insight into the nature of epistemic vices going forward.